Experiences with axial flux sheet rotor induction motor - Dwivedi A.; Gupta S.K.; Singh S.K.; Srivastava R.K. (My University, 2025)
The paper discusses experience with a 2-phase axial flux sheet rotor induction motor. The motor is a single stator solid sheet rotor induction motor. The sheet is made of Aluminium disc of 3mm thickness. The application of axial flux sheet rotor Induction motor can be extended to electric vehicles or hybrid electric vehicles due to compatible shape and easy construction. The absence of windings and bars reduces overall losses, hence increasing the efficiency of the proposed motor. Although the eddy currents induced in the sheet rotor needs to be studied. © 2015 IEEE.